Analysis of Student Skills Using Discovery Learning Based on Differences in Learning Styles - Rahmawati, Helmi; Solihah, Fatimatus; Fadli, Saiful; Fitriana, Saadatun (IKIP Mataram, 2025)
Integral is a branch of algebra included in the calculus course, making it essential to master. This research aims to analyze the skills of students with visual learning styles, auditory learning styles, and kinesthetic learning styles using discovery learning on the topic of integrals. The method used in this study is a mixed-method approach with an Explanatory Design. The first stage involves the collection and analysis of quantitative data, which takes priority in answering the research questions. The next stage is the qualitative data collection phase, where three students with different learning styles are interviewed to gain deeper insights. The results of the study indicate that learning using the discovery learning model has a significant effect on students' learning outcomes. The average score improvement of visual, auditory, and kinesthetic students shows positive results through learning using the discovery learning model, with the highest improvement seen in kinesthetic students (23.67) and visual students (22.89). The results of the mean comparison test or ANOVA (One-Way ANOVA) show that the significance value is 0.027 < 0.05, which means there is a difference in the mean posttest scores of visual, auditory, and kinesthetic students. This study demonstrates the significant impact of the discovery learning model on integral learning outcomes, revealing that visual learners outperform auditory learners, while kinesthetic learners show comparable outcomes to visual learners.